Policy analysis: food security in Malaysia - Suffian, Faridah; Suffian, Firdausi (Faculty of Administrative Science and Policy Studies, 2023)
This paper aims to explore the constraints factor in food sector in Malaysia. Various agricultural policies have been formulated to improve food production and mechanisms for channelling aid to farmers, yet the policy outcome remains abysmal. Despite Malaysia has achieved remarkable growth in its agricultural sector, however, the growth of agriculture sector prioritises the development of industrial crop commodities such as oil palm, rubber, and cocoa as major commodities at the expense of food. Thus, this has resulted in the agro-food sector being considerably underdeveloped. A qualitative study has been conducted with the objective to explore the Malaysia’s food sector performance and to examine the constraints on the sector's growth. The findings of this research reveals that mismatch priority, lack of coordination, overlapping functions and the existence of a patronage system are the root causes of the ineffectiveness of policy formulation and policy implementation. Political influence does exist in the process of policy formulation and implementation, of which affecting the direction and allocation of resources for investment in agro-food sector. Overall, this research has shown that Malaysia is facing a food security problem. Thus, the need for a policy paradigm shift towards food first policy to face a challenging future.